Effects of ultrasound and gamma irradiation on quality maintenance of fresh Lentinula edodes during cold storage. (30th March 2022) - Shi, Defang; Yin, Chaomin; Fan, Xiuzhi; Yao, Fen; Qiao, Yu; Xue, Shujing; Lu, Qi; Feng, Cuiping; Meng, Junlong; Gao, Hong
Graphical abstract: Highlights: Ultrasound and gamma irradiation produced better-quality characteristics than single treatments. Ultrasound enhanced the sterilization efficacy of gamma irradiation. Combined treatment effectively increased antioxidant capacity. Combined treatment inhibited water migration and loss. Abstract: Microbial infection, senescence and water losses result in serious quality deterioration of postharvest mushrooms. The aim of this study was to investigate the impact of ultrasound treatment (US), gamma irradiation treatment (GI) and their combination on quality maintenance of fresh Lentinula edodes during storage. The results showed that US + GI was the most effective approach to maintaining the quality of mushrooms. US + GI reduced natural microflora present on L. edodes, such as total number of colonies, molds, yeasts, Pseudomonas and Enterobacteriaceae . Furthermore, US + GI stimulated phenylalanine ammonia lyase, maintained the highest level of total phenolic content (733.63 mg GAE/kg on Day 4), and postponed the occurrence of reduced ascorbic acid (33.7% retention relative to the control), which contributed to strengthening the antioxidant capacity. Additionally, US + GI retarded water mobility and loss. In brief, the US + GI in this study is an effective hurdle technology for preserving the quality of fresh L. edodes during storage.